Conditional ablation of E‐cadherin in the oral epithelium progeny results in tooth anomalies - Stephanos Kyrkanides; Denise Trochesset; Maria Cordero‐Ricardo; Sabine M. Brouxhon (Clinical and Experimental Dental Research, 2022)
Abstract Objectives The objective of this study is to confirm the developmental origin of the enamel organ and evaluate the role of E‐cadherin in tooth development by conditional deletion in the oral epithelium and its enamel organ progeny. K5‐Cre;ROSA26 compound mice were included in this study in order to confirm the oral epithelial origin of the enamel organ, as well as of the action of the K5‐Cre transgene in ablating E‐cadherin in the enamel organ. K5‐Cre;Ecadfl/fl knockout mice were included to evaluate the effects of the conditional E‐cadherin ablation onto tooth development. Material and Methods K5‐Cre transgenic mice were crossed into the ROSA26 reporter mouse to trace the cell fate of the oral epithelium and its progeny in vivo. Moreover, K5‐Cre mice were crossed into the Ecadfl/fl mice to produce K5‐Cre;Ecadfl/fl compound mouse, as well as K5‐Cre;Ecadfl/+ and Ecadfl/fl littermate controls. These litters were euthanized at postnatal day P2 to study the effects of conditional E‐cadherin ablation in vivo. Results The K5‐Cre;ROSA26 compound mouse demonstrated that the origin of the enamel organ and the structures thereof are of oral epithelial origin. Furthermore, using the K5‐Cre;Ecadfl/fl compound mouse, we determined that conditional ablation of E‐cadherin in the oral epithelium, and its progeny, results in dental anomalies involving elongation of the molar root, shrinkage of the pulp space, and alterations of the periapical area, including cementum hyperplasia. The K5‐Cre;Ecadfl/fl mice also displayed a smaller overall stature compared with heterozygotes and wild‐type littermates. Conclusions E‐cadherin is important in tooth development, including the formation of enamel, the crown, pulp space, and the roots.